Strategi Bertahan Hidup Nelayan Kecil dalam Memenuhi Kebutuhan Hidup Pasca Kenaikan Harga BBM di Lingkungan II Kelurahan Pandan Kecamatan Pandan Kabupaten Tapanuli Tengah - Novita Andriani Panjaitan; Tuti Atika (Universitas Palangka Raya, 2024)
Fuel is one of the important components in fishing activities. The cost incurred by fishermen for fuel is estimated to reach 60-70% of the total operational costs of fishing. Fluctuations in fuel prices felt by fishermen will have an impact on the sustainability of fishing activities, especially in the economic aspect, because fuel is one of the most important factors to support fishermen's activities. This study aims to analyze the survival strategies of small fishermen in meeting their living needs after the increase in fuel prices in Environment II, Pandan Village, Pandan District. This study uses a qualitative descriptive approach. Data collection techniques are carried out by literature studies, observations, interviews and documentation. The main informants in this study were five small fishermen, the key informant was the Head of Pandan Village, and an additional informant was one of the surrounding communities. The data obtained in the field were analyzed qualitatively to obtain conclusions. The results of the study show that small fishermen in Environment II, Pandan Village, carried out several survival strategies to meet their living needs after the increase in fuel prices, namely, diversifying livelihoods, diversifying fishing gear, extending working hours, involving wives in work, minimizing expenses, borrowing money from family and neighbors, and relying on assistance provided by the government.